Comparative Study of Gender's Attitude toward the Intention to Imitate Korean Celebrity Endorsement - Wan Roazha Wan Mat; Nelson Lajuni; Amran Harun; Azaze @ Azizi Hj. Abdul Adis (2020)
The purpose of this study is to addresses the issue of how gender affecting attitude towards the intention to imitate Korean celebrity endorsement in advertisement among young Malaysians. Particularly, the researchers would like to scrutinize whether young Malaysians male and female are different attitudinally when it comes to intention to imitate Korean celebrity endorsement. A survey of 602 young consumers aged between 18 to 29 years old were participated in this study. A Multi-Group Analysis (PLS-MGA) was carried out to examine differences between two groups (male and female) in particular their intention to imitate Korean celebrity in Malaysia. The results demonstrate the comparative study of gender between male and female attitude toward the intention to imitate korean celebrity endorsement, there are no different if we want to see which characteristics, even though, whether celebrity characteristics the results is the same from male and female. However, the current researchers found that there was a different effect in terms of the level of acceptance of male and female when they affected by celebrity. The result shows that although there are relationship between attractiveness, credibility, trustworthiness, expertise, and attitude towards intention to imitate Korean celebrity endorsement, but they did not indicate major differences between male and female. In addition, there were no significant difference between male group and female group.